PENGARUH LINGKUNGAN FISIK DAN NON FISIK TERHADAP KINERJA KARYAWAN PT. JATIM JAYA PERKASA DI KECAMATAN KUBU KABUPATEN ROKAN HILIR - Adanan, Maksum; Hendriani, Susi; Daulay, Iwan Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. Jatim Jaya Perkasa located at Kecamatan Kubu Kabupaten Rokan Hilir. The population in this study were 70 employees and fully sampled so this is a research study census. The purpose of this study was to determine the effect of physical and non-physical environment on the performance of employees of PT. Jatim Jaya Perkasa at Kecamatan Kubu Kabupaten Rokan Hilir. Based on the results of the study indicate that Based on the results of the study indicate that 1) There are environmental influences physical and non-physical environment on the performance of employees of PT. Java Jaya Perkasa in Kubu district Rokan Hilir simultaneously. 2) There is the influence of the physical and nonphysical environment on the performance of employees of PT. Java Jaya Perkasa in Kubu district Rokan Hilir partially. Advice that can be given is to superiors PT. Jatim Jaya Perkasa at Kecamatan Kubu Kabupaten Rokan Hilir that should improve labor discipline through surveillance and attention to non-physical environment by giving attention not only limited to the employment relationship, but also build a sense of family properties to all employees, so that employees can work more diligently so as to increase the productivity of the company.Keywords: Physical Environment, Environmental Nonphysical, Performance.